Structured Common Project Financing (SCPF): Efficiency without debt mutualization - Christian Bauer; Marc-Patrick Adolph (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2020)
We propose Structured Common Project Financing (SCPF) as an stable, beneficial and political feasible financing tool for special purposes, e.g. Corona-Bonds, Green Deal Financing, Common Forces Budget. SCPF is an ABS-based common financing tool managed by a supranational organization like the ESM or the EIB. Our approach allows to overcome the huge and emotionally influenced political obstacle of joint liability by marginalizing the degree of jointness. SCPF creates significant interest savings compared to individual financing, 0.7% p.a. in the benchmark case. It is stable over time, robust to the emission of subgroup scenarios as e.g. a PIIGS bond and an EU-6 bond, and insensitive to the evolution of the macroeconomic environment (risk-free interest rate).
Keywords: 330; Structured Common Project Financing; Joint Liability; FiscalUnion; EMU; Sovereign Debt; ABS; Corona-Bonds